CRISIS LEADERSHIP: THE ART OF NAVIGATING ORGANIZATIONAL CHANGE DURING THE COVID-19 PANDEMIC - Prihatini, Tatik; Iswati, Sri; Suaedi, Falih (Jurnal Aplikasi Manajemen, 2022)
Organizational transformation is one of the steps leaders can take to survive and adapt to the current situation. Organizations that do not transform in a certain period will be left behind, even collapse, because of the dynamic nature of consumers and markets. Trans- formation is driven by internal factors such as the need for efficiency, revenue enhancement, and increasing employee prosperity. Meanwhile, external factors that trigger transformation include competition with competitors, technological advancement, and demand for adaptation to consumer needs and desires changes. Leaders have many references to adopt for navigating transformation in the normal situation. However, they have few references on navigating transformation in the Covid-19 pandemic situation. The Covid-19 pandemic has implied implementing a remote working system to minimize viral transmission. Such a system poses many challenges to leaders and employees as they have never practiced it. Failure of the leaders to navigate transformation will seriously harm the organization and even lead to collapse. The present study aims to identify some applicable competencies for leaders in navigating organizational transformation during the pandemic. This study used a qualitative method with semi-structured interviews as the data collection technique. The thematic analysis was conducted to analyze responses from interview questions. 14 informants were involved in this study. They consisted of general and senior managers transforming the pandemic situation. The results of this study revealed four major competencies, namely task competencies, human relation competencies, adaptive competencies, and virtual competencies in navigating transformation during the pandemic situation.